Professor: The Animal Planet Optimization - Gajawada, Satish (Review of Environment and Earth Sciences, 2014)
This paper is dedicated to everyone who is interested in making this planet a better place to live. In the past, researchers have explored behavior of several animals separately. But there is scope to explore in the direction where various artificial animals together solve the optimization problem. In this paper, Satish Gajawada proposed The AnimalPlanet Optimization. The concept of this paper is to imitate all the animals on this planet. The idea is to solve the optimization problem where all the artificial animals together solve the problem.